IOT-BASED SMART FARMING IMPLEMENTATION TO OPTIMIZE WORK EFFICIENCY OF HYDROPONIC FARMERS PAKISAJI MALANG: IMPLEMENTASI SMART FARMING BERBASIS IOT: SOLUSI MENINGKATKAN EFEKTIVITAS PETANI HIDROPONIK PAKISAJI MALANG - Latifah, Risalatul; Putro, Triswantoro; Anggraeni, Dewi; Aprilia, Faridha; Bunga Puspita, Mayang; Baroatul K, Lia (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Farmers can market their crops due to the significant market share for hydroponic agriculture products. However, this presents a dilemma as the market demands a consistent supply of high-quality crops. Precise nutrient levels and controlled chemical-physics parameters are crucial considerations in hydroponic yields. Thus far, these factors have been managed manually, leading to challenges in achieving desired outcomes. Objective: This community service program aimed to address this issue by developing a real-time automated system for monitoring and controlling chemicalphysics parameters and nutrient levels via an Android application. The goal was to enhance the effectiveness and productivity of hydroponic crop harvests. Method: The program commenced with designing the system based on farmer requirements, followed by the installation and testing of equipment at partner locations. Subsequently, technical training on system features and usage was provided. Results: The system was successfully installed at Grahaponik. According to questionnaire responses, 68.4% of farmers expressed satisfaction, and 78.9% of total participants reported that the system was easy to employ. Technology installation, implementation, and dissemination to local hydroponic farmer groups were conducted. Hydroponic farmers acknowledged the user-friendliness of the devices. Conclusion: Partners' acceptance of the instruments was favorable, facilitating their ease of use and thereby enhancing the effectiveness of hydroponic farming.